2014
DOI: 10.1186/1471-2334-14-335
|View full text |Cite
|
Sign up to set email alerts
|

Microbial aetiology, outcomes, and costs of hospitalisation for community-acquired pneumonia; an observational analysis

Abstract: BackgroundThe aim of this study was to investigate the clinical outcome and especially costs of hospitalisation for community-acquired pneumonia (CAP) in relation to microbial aetiology. This knowledge is indispensable to estimate cost-effectiveness of new strategies aiming to prevent and/or improve clinical outcome of CAP.MethodsWe performed our observational analysis in a cohort of 505 patients hospitalised with confirmed CAP between 2004 and 2010. Hospital administrative databases were extracted for all res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 25 publications
5
40
1
2
Order By: Relevance
“…Our mean costs of (≈D 5000) for hospitalized adults on the general ward are very similar to a recent smaller prospective (≈D 4000) and retrospective (≈D 4900) studies performed in the Netherlands [21,22]. Similar to our study, a study performed in the USA also showed that while the mean length of hospital stay increased with age, the costs did not increase proportionally to the length of stay in the hospital [23].…”
Section: Comparisons To Other Database Studiessupporting
confidence: 90%
See 1 more Smart Citation
“…Our mean costs of (≈D 5000) for hospitalized adults on the general ward are very similar to a recent smaller prospective (≈D 4000) and retrospective (≈D 4900) studies performed in the Netherlands [21,22]. Similar to our study, a study performed in the USA also showed that while the mean length of hospital stay increased with age, the costs did not increase proportionally to the length of stay in the hospital [23].…”
Section: Comparisons To Other Database Studiessupporting
confidence: 90%
“…Streptococcus pneumoniae is generally accepted to be the most common cause of CAP [28]. A recent Dutch study among 505 patients hospitalized with community-acquired pneumonia showed that in those cases in which a pathogen could be detected (n = 295) S. pneumoniae was causative pathogen in 42% of the cases [22]. Furthermore, data from the CAPiTA trial showed that 13% of the first episodes of community-acquired pneumonia were episodes caused by the 13 vaccine serotypes included in PCV13 [11].…”
Section: Strength and Weaknesses Of The Studymentioning
confidence: 99%
“…Two studies in Netherlands found that Streptococcus pneumoniae was the main cause of CAP, with 25% and 22% of detectable rates. But there were inconsistent detectable rates between the two studies in terms of atypical pathogens (9% and 20%) (26,27). Whereas a study in the north of Israel shows the detectable rate of atypical pathogens.…”
Section: Prevalence Of Atypical Pneumoniamentioning
confidence: 99%
“…In our discussion [1] we erroneously misclassified the study of Spoorenberg et al [2] as being a retrospective study using ICD records. Readers should know that the study of Spoorenberg et al [2] is similar to our study, a prospective cohort with confirmed CAP based on standardized diagnostic criteria.…”
Section: Erratummentioning
confidence: 99%